Evaluation of yolk sac size and embryonic heart rate in first trimester and pregnancy outcome - Tawfik, Waleed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Accurate differentiation between normal pregnancy and pregnancy loss in early gestation remains a clinical challenge-previous studies have described the association between embryonic well-beings and the characteristics of gestational sac. The aim of the study was to evaluate the yolk sac size and embryonic heart rate as a prognostic factor for the first trimester pregnancy outcome. Methods: This was a prospective cohort observesional study. It included 52 pregnant women in their first trimester from 6 week till 12 weeks gestation. Transvaginal sonographic examination after explanation and agreement of each patient. All pregnancies were followed for their pregnancy outcome after completion of 12 weeks. The adverse outcome was spontaneous miscarriage occurring before or at 12 weeks of gestation. These patients allocated into four study groups: according to gestational age at presentation and pregnancy outcome. Group I included women who were examined during (6-7 weeks+6 days). Group II included women who were examined during (8-9 weeks+6 days). Group III included women who were examined during (10-12 weeks). Group IV included women who had their pregnancies resulted into first trimester spontaneous miscarriage. Results: The validity of YS diameter regarding the prognosis of first trimester pregnancy outcome shows that; YSD had 100% specificity and 97.8% sensitivity in prediction of miscarriage. Regarding embryonic heartbeat, there was a statistically significant difference between group IV and the other groups. There was embryonic bradycardia in the miscarriage group. EHR had a sensitivity of 97.5% and specificity of 100% in prediction of first trimester pregnancy outcome. Conclusions: Abnormal yolk sac diameter, in the form of small, enlarged, absent or irregular yolk sac, and embryonic bradycardia are associated with poor pregnancy outcome.